STRUCTURAL MODEL OF COUNSELING COMPETENCE - Setiyowati, Arbin Janu; Pali, Marthen; Wiyono, Bambang Budi; Triyono, Triyono (LPMPP Universitas Negeri Yogyakarta, 2019)
Counseling competence is a set of essential abilities which is prominent to be employed in conducting counseling. This counseling competence research took students of counseling as a counselor candidate. This study aims to analyze the correlation between basic knowledge, basic communication skill, and cultural skill to the counseling competence. This work used Ex Post Facto Causal Relationship Explanatory research design. The research subjects were 120 students of Department of Guidance and Counseling from three State Universities in Java Island. Samples were taken by using cluster random sampling technique. The data analysis was conducted through Structural Equation Modeling (SEM) technique. The research results show that there is a significant relationship between knowledge, basic attitude, basic communication skill and cultural skill to the counseling competence. The implication of this research finding to the education of the Department of Guidance and Counseling is the significance of considering the factors forming the academic counseling competence to produce the professional counselor candidate.